2020
DOI: 10.9734/afsj/2020/v19i330239
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Chemical Composition of Three Different Eggplant Fruit Species

Abstract: Chemical composition of three different eggplant fruit species was studied using standard methods. Solanum aethiopicum, Solanum melongena and Solanum macrocarpon fruit species were used as samples. Results obtained showed high moisture, phytate and oxalate contents in the investigated fruit species. Vitamin concentrations of the investigated fruits ranged from high to low. One or two of the investigated fruits possessed a higher amount of the chemical compounds than others. This study has shown the comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…However, it is worth mentioning that some saponins cannot produce foam [ 75 ]. In addition, Benjamin et al [ 76 ] reported a total saponin content of 5.34 mg/100 g in eggplant ( S. melongena ) fruit, values lower than those found in the different parts of the eggplant residue plant. On the other hand, Hamzah et al [ 15 ] reported higher values (64 mg/100 g) in ripe eggplant fruits than in residual eggplant fruit.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is worth mentioning that some saponins cannot produce foam [ 75 ]. In addition, Benjamin et al [ 76 ] reported a total saponin content of 5.34 mg/100 g in eggplant ( S. melongena ) fruit, values lower than those found in the different parts of the eggplant residue plant. On the other hand, Hamzah et al [ 15 ] reported higher values (64 mg/100 g) in ripe eggplant fruits than in residual eggplant fruit.…”
Section: Resultsmentioning
confidence: 99%